Genetic Plurality of OXA/NDM-Encoding Features Characterized From Enterobacterales Recovered From Czech Hospitals - Chudejova, Katerina; Kraftova, Lucie; Mattioni Marchetti, Vittoria; Hrabak, Jaroslav; Papagiannitsis, Costas C.; Bitar, Ibrahim (Frontiers in Microbiology, 2021)
The aim of this study was to characterize four Enterobacterales co-producing NDM- and OXA-48-like carbapenemases from Czech patients with travel history or/and previous hospitalization abroad. Klebsiella pneumoniae isolates belonged to ‘high risk’ clones ST147, ST11 and ST15, while the Escherichia coli isolate was assigned to ST167. All isolates expressed resistance against most β-lactams, including carbapenems, while retaining susceptibility to colistin. Furthermore, analysis of WGS data showed that all four isolates co-produced OXA-48- and NDM-type carbapenemases, in different combinations (Kpn47733: blaNDM-5+blaOXA-181; Kpn50595: blaNDM-1+blaOXA-181; Kpn51015: blaNDM-1+blaOXA-244; Eco52418: blaNDM-5+blaOXA-244). In Kpn51015, the blaOXA-244 was found on plasmid p51015_OXA-244, while the respective gene was localized in the chromosomal contig of E. coli Eco52418. On the other hand, blaOXA-181 was identified on a ColKP3 plasmid in isolate Kpn47733, while a blaOXA-181-carrying plasmid being an IncX3-ColKP3 fusion was identified in Kpn50595. The blaNDM-1 gene was found on two different plasmids, p51015_NDM-1 belonging to a novel IncH plasmid group and p51015_NDM-1 being an IncFK1-FIB replicon. Furthermore, the blaNDM-5 was found in two IncFII plasmids exhibiting limited nucleotide similarity to each other. In both plasmids, the genetic environment of blaNDM-5 was identical. Finally, in all four carbapenemase-producing isolates, a diverse number of additional replicons, some of these associated with important resistance determinants, like blaCTX-M-15, arr-2 and ermB, were identified. In conclusion, this study reports the first description of OXA-244-producing Enterobacterales isolated from Czech hospitals. Additionally, our findings indicated the genetic plurality involved in the acquisition and dissemination of determinants encoding OXA/NDM carbapenemases.